2016
DOI: 10.5507/euj.2016.006
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness of individuals with intellectual disability who have Special Olympics experience

Abstract: Physical fitness of individuals with intellectual disability (ID) is low compared to those without ID. Part of the mis sion of Special Olympics is to develop physical fitness. However, little is known about fitness levels of Special Olympics athletes. This study examined the fitness level of individuals who participated in Nordic Special Olympics Games 2008 in Finland. The sample consisted of 59 Special Olympics athletes (44 men, 15 women, age 16-45) whose fitness scores were compared to INASathletes (Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These authors found that males consistently outperformed females in abdominal strength and endurance. Similar sexbased strength differences were documented more recently in a sample of Nordic Special Olympics athletes (Rintala et al, 2016). However, the small number of female athletes (n = 79 in the Cuesta-Vargas et al study, n = 33 in the Lahtinen et al study,and n = 15 in the Rintala et al study), limits our understanding of sex-related differences.…”
Section: Muscular Strength Among Adults With An Intellectual Disabilitysupporting
confidence: 59%
See 1 more Smart Citation
“…These authors found that males consistently outperformed females in abdominal strength and endurance. Similar sexbased strength differences were documented more recently in a sample of Nordic Special Olympics athletes (Rintala et al, 2016). However, the small number of female athletes (n = 79 in the Cuesta-Vargas et al study, n = 33 in the Lahtinen et al study,and n = 15 in the Rintala et al study), limits our understanding of sex-related differences.…”
Section: Muscular Strength Among Adults With An Intellectual Disabilitysupporting
confidence: 59%
“…Despite the importance of strength, individuals with an ID have a lower level of strength than their general-population peers (Cuesta-Vargas et al, 2011;Lahtinen et al, 2007); these lower levels include individuals with an ID who are athletes (Cuesta-Vargas & Hilgenkamp, 2015). Additionally, among individuals with an ID, there is some evidence that strength decreases with age (Lahtinen et al, 2007;Oppewal et al, 2014b) and that females have lower eujapa.upol.cz muscle strength than their male peers (Cuesta-Vargas et al, 2011;Lahtinen et al, 2007;Rintala et al, 2016). For example, Cuesta-Vargas and colleagues found that male Special Olympics athletes scored higher than female athletes on the following muscular strength and endurance tests: timed sit to stand, partial sit-up test, seated push-up test, and the hand grip test.…”
Section: Muscular Strength Among Adults With An Intellectual Disabilitymentioning
confidence: 99%
“…To assess muscle strength, three different tests were selected: (i) Grip Strength (GS), (ii) 30 s Sit Up (SUP), and (iii) the Timed Stand Test (TST). The use of three tests was justified by the need to assess different manifestations of strength and different muscle groups as a basis for determining a person’s PF [ 2 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with intellectual disabilities (ID) generally show lower levels of physical fitness (PF) than those without disabilities of the same sex and age [ 1 , 2 , 3 , 4 ]. However, making comparisons between values obtained by individuals without disabilities and individuals with disabilities could imply a comparative disadvantage for the latter because the personal and social development as well as the characteristics of adults with and without ID are not similar.…”
Section: Introductionmentioning
confidence: 99%
“…Most definitions of physical fitness incorporate body composition, cardiorespiratory endurance, muscular strength and endurance, and flexibility [ 11 ]. These physical aspects are essential for performing activities of daily living and developing functional skills, and low levels of cardiorespiratory fitness and muscular strength and endurance can limit independence in adulthood [ 12 ].…”
Section: Introductionmentioning
confidence: 99%